Flood embankments monitoring system = System monitorowania wałów przeciwpowodziowych - Michta, Emil; Piotrowski, Krzysztof; Powroźnik, Piotr; Rybski, Ryszard; Szulim, Robert; Kołodziejczyk, Urszula; Kostecki, Jakub (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents a concept of a system of continuous monitoring of flood embankments with the use of currently available ICT technologies. Architecture and the system description as well as benefits resulting from its implementation were presented.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne